The Relation Between Macronutrient Adequency Level Mother`s Personal Hygiene, Environmental Sanitation and Diarrhea with Stunting Incidences Among Childern Aged 24-59 Months - Sari, Yulianti Wulan; Wirjatmadi, Bambang; Setyaningtyas, Stefani Widya (Tadulako University, 2020)
Stunting is a undernutrition chronic status in the period of growth and development since the beginning of life. The incidence of stunting is influenced by multifactorial. Some factors such as the adequacy of macro nutrition during the growth period, incidence of infectious diseases, maternal personal hygiene and environmental sanitation, and mother's education, mother's occupation and family income. The purpose of this study was to analyze the adequancy of macro nutrient, incidents of diarrhea, maternal personal hygiene, and environmental sanitation for the incidence of stunting. This research was observational with a case-control design. The case group was stunting toddlers aged 24-59 months, whereas the control group was normal toddlers (H/A) toddler age 24-59 months. Research was carried out in the working area of Mulyorejo Health Center Surabaya. Sample on this research was 28 for both stunting and non-stunting. Data was collected by measuring height and weight, family and toddler characteristic questionnaire, personal hygiene behavior assessment questionnaire, healthy home assessment questionnaire, food recall questionnaire 1x24 hours on holidays and week days. The data were analyzed using chi-square tests to determine the correlection of variabels on the incidence of stunting. The results of the study showed that there is a relationship between the level of energy sufficiency (p = 0.015) (OR = 4,636), the level of protein sufficiency (p = 0,000) (OR = 15,000), the level of fat sufficiency (p = 0,000) (OR = 22,000), the level of carbohydrate adequacy (p = 0,000) (OR = 11,500), history of diarrhea (p = 0.001) (OR = 0.121), and maternal personal hygiene (p = 0,000) (OR = 0.263) with stunting but, was no relationship between environmental sanitation (p = 0.070) (OR = 0.258) for the incidence of stunting. The conclusion in this study is the adequacy of macro nutrients, no incidents of diarrhea, good maternal personal hygiene, and environmental sanitation that meet the requirements will reduce the risk of stunting